2005
DOI: 10.4028/www.scientific.net/kem.284-286.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Physical-Chemical Variables in the Synthesis of Hydroxyapatite by the Precipitation Route

Abstract: Abstract. The synthetic hydroxyapatite is a very useful material for numerous applications in medicine as a biomaterial. One of the most economic manufacturing process is the precipitation route. In the present work, synthetic hydroxyapatite was prepared using the precipitation route, starting with aqueous solutions of calcium nitrate (Ca(NO 3 ).4H 2 O ) and ammonium phosphate (H 2 (PO 4 )NH 4 ). The effects of physical-chemical variables such as pH, temperature, time of agitation, ageing time and heat treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…When as-synthesized particles remain in solution over time, irreversible changes usually occur such as growth and crystallization of the primary particles. [19][20][21] Thereby, the change in different parameters allows to obtain phosphates with different sizes, shapes and crystallinity or acidity character. [20][21][22][23] Several works on phosphate synthesis are reported in the literature [24][25][26][27] and some of them are focused on aluminum phosphate synthesis [28][29][30] and its thermal evolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When as-synthesized particles remain in solution over time, irreversible changes usually occur such as growth and crystallization of the primary particles. [19][20][21] Thereby, the change in different parameters allows to obtain phosphates with different sizes, shapes and crystallinity or acidity character. [20][21][22][23] Several works on phosphate synthesis are reported in the literature [24][25][26][27] and some of them are focused on aluminum phosphate synthesis [28][29][30] and its thermal evolution.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Thereby, the change in different parameters allows to obtain phosphates with different sizes, shapes and crystallinity or acidity character. [20][21][22][23] Several works on phosphate synthesis are reported in the literature [24][25][26][27] and some of them are focused on aluminum phosphate synthesis [28][29][30] and its thermal evolution. 31 However, most studies refer to the orthophosphate case as has been mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the nature and type of the mineral crystals are believed to be determined by the pH and initial Ca/P ratio, because the pH determines the relative ratios among H 2 PO 4 − , HPO 4 2− , and PO 4 3− . It has been reported that formation of HAP preferentially occurs at relatively high pH values, e.g., 10−12, [61][62][63]66 while HAP may also be formed at low pH values using a complexing agent or premixed HAP particles as seeds. 67,68 A significant body of literature has described the formation of HAP at elevated temperatures, followed by prolonged aging and sintering.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Solubility isotherms suggest the pH conditions required for the synthesis of specific CaPs, for example see [8]. HA is the least soluble CaP phase above pH 4.5 and precipitation has been reported between pH levels of 7.5 and 12.5 [9][10][11][12][13][14][15]. Under physiological conditions (37°C and pH 7.4) HA exhibits the lowest solubility and thus slowest dissolution rate followed by β-tricalcium phosphate [β-Ca 3 (PO 4 ) 2 -(β-TCP)].…”
Section: Introductionmentioning
confidence: 98%